Family Strategies for Nurturing Aswaja Aqidah in Children: A Qualitative Study of Tastafi Muslimah Congregants in Banda Aceh - Ainun, Ainun; Basri, Hasan; Hanafiah, Muhibuddin; Harmaini, Harmaini (FITRAH: International Islamic Education Journal, 2025)
Aqidah is a fundamental aspect in shaping Islamic character and identity; however, in the era of Society 5.0, challenges such as moral degradation, technological penetration, and the influence of globalization pose significant risks to young people’s understanding of religious creed. Tastafi Muslimah, as part of the broader Tastafi learning network, plays an essential role in strengthening Aswaja-based aqidah education by providing religious guidance to mothers as the primary educators within the family. This study aims to analyze the patterns of Aswaja aqidah cultivation in Tastafi families, the implementation of Aswaja principles in children, and the supporting and inhibiting factors that influence aqidah learning in the household. Using a descriptive qualitative approach, data were collected through observation, in-depth interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that Aswaja aqidah development is carried out through the introduction of core tawhid concepts, parental religious role modeling, the habituation of worship practices, and the creation of a supportive social environment. The implementation of Aswaja principles is reflected in the reinforcement of religious values, character building, and the involvement of the Tastafi community as an extended religious learning space. Supporting factors include family commitment and community involvement, while inhibiting factors involve digital influences, unsupportive social environments, and limited parental supervision. These findings affirm that Tastafi families hold a strategic role in ensuring the continuous transmission of Aswaja aqidah through the synergy between religious parenting practices and community-based support systems.